Teknik Reframing Dalam Mereduksi Perilaku Agresif Remaja Dengan Konseling Individu (Studi Kasus Klien “D” Di Kelurahan Pahlawan Palembang) - Nopriyansah, Randi; Kusnadi, Kusnadi; Jannati, Zhila (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
This research is motivated by aggressive behavior by teenagers in the Heroes Village. This study aims to determine the description of aggressive behavior of client "D" before individual counseling with reframing techniques, to determine the factors that influence aggressive behavior of client "D", to know how the application of individual counseling with reframing techniques in reducing aggressive behavior of client "D", to know the behavior aggressive client "D" after individual counseling with reframing techniques. This study uses a qualitative approach with a case study research method. The subject in this study is client "D". Data collection techniques are using observation, interviews, and documentation. While the data analysis technique uses pattern matching, explanation making, and time series analysis. The results of this study indicate that before individual counseling is carried out it was still in the high category, which can be seen from some of the behaviors carried out by client "D" they cannot control their emotions, are easily influenced by the environment, like to refuse when asked to, and have feelings of suspicion and resentment towards others. And also influenced by internal and external factors. The application of individual counseling is carried out in six meetings where each meeting uses three stages, namely the initial stage, the core or work stage and the final stage. The description of client “D” aggressive behavior after individual counseling with reframing techniques is that the aggressive behavior has been reduced, client “D" is able to be more calm and patient in dealing with things, is more able to choose what is good or bad for himself, is starting to able to not refuse when asked to, and no longer has feelings of grudges and suspicion of other people.